Perancangan Sistem Otomatis Pompa Air Menggunakan Frekwensi Radio 27 MHz - Tafrikhatin, Asni; Kurniawan, Eko; Muslihin, Rifki; Kusworo, Sugeng (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2021)
The need for water is one of the basic human needs. Humans often do not realize that they have wasted water for things that are less useful. Water saving should be realized by the general public. One way to save water is by not forgetting to turn off the water when the water is full in the water reservoir. The problem of often forgetting to turn off the water is one of the main factors. This research method consists of problem identification, product design, product testing, and product evaluation. The product made in this research is WLC using a radio frequency of 27 MHz. Based on the test results, this radio frequency can work from a distance of 1 meter to 5 meters. WLC with radio frequency is expected to be a cheap alternative to WLC types.